2012
DOI: 10.1038/aja.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in HIF1A are associated with prostate cancer risk in a Chinese population

Abstract: The hypoxia-inducible factor-1α (HIF-1α) plays an important role in regulating angiogenesis, which is essential for tumor growth and metastasis. Genetic variations of HIF1A (coding HIF-1α) have been shown to influence an individual's susceptibility to many human tumors; however, evidence on associations between HIF1A single-nucleotide polymorphisms (SNPs) and prostate cancer (PCa) risk is conflicting. We genotyped three potentially functional polymorphisms in HIF1A (rs11549465, rs11549467 and rs2057482) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…In another case-control study, they have observed the significant associations of SNP rs2057482 with risk of rectal cancer (Frank et al, 2010). In addition, another study has demonstrated that the combined variant genotypes of rs2057482 and rs11549467 are associated with increased prostate cancer risk (Li et al, 2012). However, hardly any studies have been performed to find the association between SNP rs2301113 and cancers.…”
Section: Discussionmentioning
confidence: 93%
“…In another case-control study, they have observed the significant associations of SNP rs2057482 with risk of rectal cancer (Frank et al, 2010). In addition, another study has demonstrated that the combined variant genotypes of rs2057482 and rs11549467 are associated with increased prostate cancer risk (Li et al, 2012). However, hardly any studies have been performed to find the association between SNP rs2301113 and cancers.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, two polymorphisms, namely, the C1772T (P582S) and G1790A (A588T) polymorphisms of the HIF-1α gene have been reported to significantly increase gene transcriptional activity, leading to an increased expression of HIF-1α mRNA and protein [27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…We analysed a functional SNP (+1772 C>T) in the HIF1A gene in prostate cancer patients and controls and found lack of association, although a relatively large population with approximately 1500 men was analysed. Concordantly, two large case-control studies from the United States of America and China also observed no risk for having PCa in carriers of this polymorphism [19,26], even though opposite results have been also reported [16,27]. The C-by-T substitution in the +1772 locus at the oxygen-dependent domain of the HIF1A gene results in a proline-to-serine substitution and was shown to stabilise HIF1A and enhance its activity as a transcription factor in both normoxia and hypoxia [12,28].…”
Section: Discussionmentioning
confidence: 69%